At the Gates: The Tantalum-Rich Phase Hf3Ta2O11 and its Commensurately Modulated Structure - Wiedemann, Dennis; Lüdtke, Tobias; Palatinus, Lukáš; Willinger, Elena; Willinger, Marc G; Mühlbauer, Martin J; Lerch, Martin (Inorganic chemistry, 2018)
Generic mixtures in the system (Zr,Hf)O2-(Nb,Ta)2O5 are employed as tunable gate materials for field-effect transistors. Whereas production processes and target compositions are well-defined, resulting crystal structures are vastly unexplored. In this study, we summarize the sparse reported findings and present the new phase Hf3Ta2O11 as synthesized via a sol-gel route. Its commensurately modulated structure represents the hitherto unknown, metal(V)-richest member of the family (Zr,Hf) x(Nb,Ta)2O2 x+5. Based on electron, neutron, and X-ray diffraction, the crystal structure is described within modern superspace [Hf1.2Ta0.8O4.4, Z = 2, a = 4.7834(13), b = 5.1782(17), c = 5.064(3) Å, q = 1/5 c*, orthorhombic, superspace group Xmcm(00γ) s00] and supercell formalisms [Hf3Ta2O11, Z = 4, a = 4.7834(13), b = 5.1782(17), c = 25.320(13) Å, orthorhombic, space group Pbnm]. Transmission electron microscopy shows the microscopic structure from film-like aggregates down to atomic resolution. Cation ordering within the different available coordination environments is possible, but no significant hint at it is found within the limits of standard diffraction techniques. Hf3Ta2O11 is an unpredicted compound in the above-mentioned oxide systems, in which stability ranges have been disputably fuzzy and established only by syntheses via solid-state routes so far.